1998
DOI: 10.1002/pro.5560070705
|View full text |Cite
|
Sign up to set email alerts
|

MgATP binding to the nucleotide‐binding domains of the eukaryotic cytoplasmic chaperonin induces conformational changes in the putative substrate‐binding domains

Abstract: The eukaryotic cytosolic chaperonins are large heterooligomeric complexes with a cylindrical shape, resembling that of the homooligomeric bacterial counterpart, GroEL. In analogy to GroEL, changes in shape of the cytosolic chaperonin have been detected in the presence of MgATP using electron microscopy but, in contrast to the nucleotide-induced conformational changes in GroEL, no details are available about the specific nature of these changes. The present study identifies the structural regions of the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Intriguingly, the ␣WT complex digested with thermolysin retained its quaternary structure and was able to capture denatured GFP but did not exhibit ATP-dependent folding activity (data not shown). These results are fully consistent with the previous findings for CCT (10). Similar results were obtained in the experiments using proteinase K (Fig.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Intriguingly, the ␣WT complex digested with thermolysin retained its quaternary structure and was able to capture denatured GFP but did not exhibit ATP-dependent folding activity (data not shown). These results are fully consistent with the previous findings for CCT (10). Similar results were obtained in the experiments using proteinase K (Fig.…”
Section: Resultssupporting
confidence: 93%
“…However, the exact relationship between the nucleotide-bound state and the conformation is still controversial in group II chaperonins. Szpikowska et al (10) reported that CCT is more resistant to trypsin digestion at the apical domain in the presence of ATP than in the absence of nucleotide and the presence of AMP-PNP, and the AMP-PNP-bound form of CCT is trypsin-sensitive as is the nucleotide-free form. On the other hand, Llorca et al (11) showed that the binding of AMP-PNP to CCT results in the cavity being closed off by the helical protrusions of the apical domains.…”
mentioning
confidence: 99%
“…Addition of ATP induces formation of the closed lid, which confines the substrate in the central cavity. Experiments with nonhydrolyzable analogs of ATP indicate that ATP binding alone does not promote closure of the lid [11,39]. Nevertheless, these non-hydrolyzable nucleotides do induce a conformational change in TRiC, which is observed by tryptophan fluorescence [40], which might, in turn, affect the conformation of the bound substrate (Figure 3b).…”
Section: Nucleotide-induced Conformational Changes In Tricmentioning
confidence: 99%
“…2a, left gel). Notably, cleavage occurred at a position in the Cpn lid equivalent to that cleaved in TRiC subunits 27 . Incubation with ATP, but not ADP, triggers lid closure, resulting in protection of the lid segments (Fig.…”
Section: The Lid Couples Atp Hydrolysis To Substrate Foldingmentioning
confidence: 99%